Potencial inovador e desenvolvimento econômico : uma análise da economia do Rio Grande do Sul - Souza, Gabriel Ribeiro de (2022)
This study aims to identify some of the main variables that explain the economic development of the municipalities of Rio Grande do Sul (RS), considering the location of activities within the state and the role of these activities in generating innovations. Therefore, Exploratory Spatial Data Analysis (ESDA) was used with the objective of identifying clusters of innovation and development and, later, regressions were carried out in order to analyze the role that the potential in generating innovations, the presence of technology parks, the urbanization and the productive diversification have on the economic development of municipalities and their respective regions. The ESDA indicated that the innovative potential and economic development within the state have a positive relation with the regions in which they are located, allowing the identification of clusters in the main urban areas of the state. The econometric modeling showed that factors such as potential to generate innovations, urbanization of municipalities and the presence of technology parks brought positive results for economic development in RS. On the other hand, the diversification of activities did not bring conclusive results, indicating that there is some limitation in generating benefits that affect different sectors of the economy.